Financial Management for Students in Semarang City - Nur Chasanah, Amalia; Puspitasari, Diana; Rizky Aurinaya, Angelia (CV. AFDIFAL MAJU BERKAH, 2024)
The increasingly sophisticated technology of today has brought about a number of developments, notably in the financial industry. Effective financial management is essential for change adaptation. This study attempts to examine the impact that self-control, attitudes, and knowledge have on students' financial management. Two hundred students from the city of Semarang served as the sample for this study. Multiple linear regression analysis approaches are used in data processing with the SPSS program. The findings show that while the attitude variable has no discernible impact on financial management, the knowledge and self-control factors have a positive and significant influence on it. The study's adjusted R square value indicated that knowledge, attitude, and self-control variables accounted for 78.9% of the variation in financial management variables, with other variables outside the scope of the research influencing the remaining 21.1%.